IMPLEMENTASI AKUNTANSI LINGKUNGAN TERHADAP PENGELOLAAN LIMBAH RUMAH SAKIT SILOAM JEMBER - Cintia Wulandari; Alwan Sri Kustono; Norita Citra Yuliarti (Juremi: Jurnal Riset Ekonomi, 2021)
Environmental accounting is an accounting treatment with the inclusion of environmental cost into the accounting practices of companies or government agencies. Hospital are service companies engaged in the health sector which in their operations can have a positive or negative impact on the community in the form of waste. Hospital waste is all waste generated by a hospital as a result of its operational activities which can contain hazardous and toxic active ingredients that can transmit disease. This study aims to determine how the application and differences of environmental accounting on waste management at Siloam Jember Hospital are related to identification, measurement, recognition, presentation, and disclosure. The type of research use in this research is descriptive qualitative. The data obtained in this study are based on primary data in the form of interview and observations, and based on secondary data in the form of documentation which will then be compared with PSAK No. 33 about General Mining Accounting. The results of this study indicate that the costs incurred as a result of hospital waste management consist of machine procurement costs, maintenance costs, repair costs, depreciation costs, and transportation service costs.